2011
DOI: 10.1007/s00425-011-1543-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the bacterial heavy metal transporter MerC fused with a plant SNARE, SYP121, in Arabidopsis thaliana increases cadmium accumulation and tolerance

Abstract: The bacterial merC gene from the Tn21-encoded mer operon is a potential molecular tool for improving the efficiency of metal phytoremediation. Arabidopsis SNARE molecules, including SYP111, SYP121, and AtVAM3 (SYP22), were attached to the C-terminus of MerC to target the protein to various organelles. The subcellular localization of transiently expressed GFP-fused MerC-SYP111, MerC-SYP121, and MerC-AtVAM3 was examined in Arabidopsis suspension-cultured cells. We found that GFP-MerC-SYP111 and GFP-MerC-SYP121 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…With molecular engineering, now it may be possible to derive strains with improved performance even under stressful field conditions. Kiyono et al (2012) isolated bacterial merC gene (a potential molecular tool) for improving the efficiency of cadmium phytoremediation. Arabidopsis thaliana protein receptors including SYP111/ SYP121 and SYP22 attached to the C-terminus of MerC and targeted foreign molecules to the plasma membrane and vacuolar membrane, respectively.…”
Section: Biostimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…With molecular engineering, now it may be possible to derive strains with improved performance even under stressful field conditions. Kiyono et al (2012) isolated bacterial merC gene (a potential molecular tool) for improving the efficiency of cadmium phytoremediation. Arabidopsis thaliana protein receptors including SYP111/ SYP121 and SYP22 attached to the C-terminus of MerC and targeted foreign molecules to the plasma membrane and vacuolar membrane, respectively.…”
Section: Biostimulationmentioning
confidence: 99%
“…Arabidopsis thaliana (microbe merC gene assisted) Cd Kiyono et al (2012) however, more effective and commercially feasible techniques are still required to make phytotechnology more commercially attractive. Conesa et al (2012) have suggested the exploitation of new economic opportunities such as the production bioenergy, biochar and biofortified crops, the application of economic studies and economic evaluations as well as a new implementation protocol in the field of phytotechnologies.…”
Section: Celocia Cristata Helianthus Annuus Tagetes Patulamentioning
confidence: 99%
“…At the appropriate time, the medium was supplemented with 25 µg/mL kanamycin or 0.5 µM mercuric chloride as described previously. 16) Arabidopsis thaliana ecotype Columbia (Col-0) and T 3-5 progeny of merC (C10), merC-SYP121 (CS17), or merC-AtVAM3 (CV11) transgenic plants expressing MerC and MerC fused with plant SNAREs, 12) respectively, were used in this study. The plant assay medium contained 1/10 strength Hoagland medium [0.28 mM Ca(NO 3 ) 2 , 0.6 mM KNO 3 ,…”
Section: Materials and Plant Assay Conditionsmentioning
confidence: 99%
“…In a previous study, genetically engineered Arabidopsis plants were obtained by fusing bacterial merC gene to genes encoding plant SNAREs, and the resultant plants were able to express MerC in specific membranes. The fusion of merC to SYP121 results in a fusion protein that can be expressed on the plasma membrane, while fusing merC to AtVAM3 enables the fusion protein to be expressed on vacuolar membranes.12) The expression of MerC-SYP121 in genetically engineered Saccharomyces or Arabidopsis resulted in significant accumulation of Cd(II) 12,13) and Hg(II) 14,15) as well as in the protection of the organism from metal-induced toxicity.Removal of methylmercury from the environment is important because inorganic mercury is converted to methylmercury upon methylation, and this is subsequently bioaccumulated in the nature through the food chain. However, it is difficult to effectively remove methylmercury from the environment by phytoremediation because a methylmercury transport system has not yet been discovered in plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation